Answer:
the answer is (x,y) = (6,6)
Explanation:
1) first solve the equation for 2y
you should've gotten:
2y = -6 + 3x
5x - 2y = 18
2) substitute the value of 2y into the equation
5x - 2y = 18
so, 5x -(-6 + 3x) = 18
3) now solve 5x -(-6 + 3x) = 18
4) from that solving that equation, u should've gotten x = 6
5) now plug in 6 for x in the other equation, solve for y
( • stands for multiplication if u didn't know, we use this in higher levels of math so multiplication symbols and x variables aren't confused)
5 • 6 - 2y = 18
6) after solving for y in the previous equation, u should've gotten y = 6
7) now we know that x = 6 and y = 6, however it is always important to check if ur answer is correct by plugging in the x value y values u ended up with into the original system of equations.
checking ur work would look something like this:
2(6) = -6 + 3(6)
5(6) - 2(6) = 18
hope this helps <3